Footing in human-robot conversations: how robots might shape participant roles using gaze cues - Mutlu, Bilge; Shiwa, Toshiyuki; Kanda, Takayuki; Ishiguro, Hiroshi; Hagita, Norihiro (2009 4th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2009)
During conversations, speakers establish their and others' participant roles (who participates in the conversation and in what capacity)--or "footing" as termed by Goffman-using gaze cues. In this paper, we study how a robot can establish the participant roles of its conversational partners using these cues. We designed a set of gaze behaviors for Robovie to signal three kinds of participant roles: addressee, bystander, and overhearer. We evaluated our design in a controlled laboratory experiment with 72 subjects in 36 trials. In three conditions, the robot signaled to two subjects, only by means of gaze, the roles of (1) two addressees, (2) an addressee and a bystander, or (3) an addressee and an overhearer. Behavioral measures showed that subjects' participation behavior conformed to the roles that the robot communicated to them. In subjective evaluations, significant differences were observed in feelings of groupness between addressees and others and liking between overhearers and others. Participation in the conversation did not affect task performance-measured by recall of information presented by the robot-but affected subjects' ratings of how much they attended to the task.